Evaluation of different models for validating of photovoltaic cell temperature under semi-arid conditions. Issue 12 (December 2021) - Lamaamar, Ibtissam; Tilioua, Amine; Ben Zaid, Zaineb; Babaoui, Abdelhak; Ettakni, Mahmoud; Hamdi Alaoui, Moulay Ahmed
Abstract: Photovoltaic (PV) solar energy enables direct production of electricity. The photovoltaic effect produced in the solar cells converts light energy from the sun's rays into electricity. Some of the solar radiation absorbed by a PV module is not converted into electricity but takes the form of an increase in the temperature of the module, reducing its electrical efficiency. The operating temperature of PV modules generally affects the performance of the PV system; performance also depends on numerous variables such as ambient temperature, wind speed, wind direction, total irradiance, dust accumulating on the PV module face and relative humidity. In this study different models for predicting the operating temperature of PV modules have been investigated. The models' relevance to PV module technology and climatic conditions in Errachidia city (coordinates: 31° 55′ 55″ north, 4° 25′ 28″ west) in the Drâa Tafilalet region was examined. The models that factor in wind data predict PV cell temperature better than the standard approach which does not include wind data. The models' accuracy was estimated based on R 2 and RMSE values. A model is more accurate the higher the R 2 is and the lower the RMSE is. In addition, we noticed that the models investigated are more accurate for a short time period during the day. Abstract : Photovoltaic module; Module temperature; prediction models; Temperature measured.